Underdiagnosed asthma in South Australia. Issue 10 (26th September 2003) - Adams, R J; Wilson, D H; Appleton, S; Taylor, A; Dal Grande, E; Chittleborough, C R; Ruffin, R E
Abstract : Background: The prevalence of undiagnosed asthma in the general population and the clinical and demographic characteristics of these patients compared with those with diagnosed asthma are unclear. Methods: The North West Adelaide Health Survey (NWAHS) is a population household interview survey of adults (age >18 years) in the north western suburbs of Adelaide, South Australia (regional population 0.6 million). Data obtained were weighted to the closest census data to provide population representative estimates. Positive answers to: "Have you ever had asthma?"; "Has it been confirmed by a doctor?"; "Do you still have asthma?" determined current physician diagnosed asthma. A positive bronchodilator response on spirometric testing according to ATS criteria without a physician's diagnosis determined undiagnosed asthma. Other measures included the SF-12 health survey questionnaire, the Selim index of severity of chronic lung disease, skin allergy tests, and demographic data. Results: Of the 3422 individuals interviewed, 2523 (74%) agreed to participate in the clinical assessment. Of these, 292 (11.6%) had asthma, 236 (9.3%) with a doctor's diagnosis of asthma and 56 (2.3%) with undiagnosed asthma defined on spirometric criteria; thus, 19.2% of the total asthma group were undiagnosed. Those undiagnosed were more likely (p<0.05) to be >40 years old, on government benefits, with an income <AUD40 000. Symptom frequency was similar in the two asthma groups, but mean spirometric values were lower in the undiagnosed group (p<0.05) while positive skin allergy tests were more common in the diagnosed group (p<0.05). SF-12 component summary scores were significantly lower in both asthma groups than in the non-asthma population. Undiagnosed asthma was frequent in men and in those aged >65 years. Health service use over the previous year was similar for both asthma groups. Conclusion: Undiagnosed asthma is common among the Australian population, with a similar clinical spectrum to those with diagnosed asthma.